Examining the problem solving skills and assertiveness characteristics of physical education teachers working in secondary and high schools according to certain variables - KARATUT, Adem; TAPŞIN, Fuat Orkun; ÇAKMAK, Gökhan; SELVİ, Sabit; TAPŞIN, Faik Orhun (Progress in Nutrition, 2022)
Study Objective: The purpose of this study is to examine the problem-solving skills and assertiveness characteristics of physical education teachers working in secondary and high schools. Methodsː The sample group of the study consisted of physical education teachers working in Çayırova district of Kocaeli province and Adapazarı district of Sakarya province. The data were collected through Google Forms. The number of participants reached in this way is 139. SPSS 20.0 package program has been used to analyze the data. Besides descriptive statistics, T Test and ANOVA Test have been used in the analysis of the data because the data were distributed normally. Results: While there is a significant relationship in favour of males in the evaluative approach of the problem solving skills of physical education teachers in primary and secondary schools, a significant difference was found in favour of married individuals in assertiveness levels. Conclusionsː As a result of the study, while there was a significant difference in favour of males in the evaluative approach of problem solving skills, no significant relationship was found in other sub-dimensions.